BASLAWÌSH KLASS OQÌWSHÌLARÌ USHÌN EKOLOGIYALÍQ TÁLIM: MAZMUNÌ HÁM PEDAGOGIKALÌQ STRATEGIYALARÌ - Allayarov, M.J. (SCIENCE and SOCIETY, 2024)
This study investigates the content and pedagogical strategies essential for effective environmental education in primary schools. By analyzing current practices and challenges through surveys, classroom observations, the research identifies key topics such as biodiversity, ecosystems, recycling, climate change as crucial for young learners. The study concludes that a well-rounded, interactive curriculum is vital for fostering environmental awareness and responsible behavior in primary school pupils.
Keywords: ecological education; environmental education; primary school; biodiversity; ecosystems; recycling; climate change